"You're Capped!" Understanding the Effects of Bandwidth Caps on Broadband Use in the Home - Chetty, Marshini; Banks, Richard; Brush, A.J.; Donner, Jonathan; Grinter, Rebecca E. (ACM Conference on Human Factors in Computing Systems, 2012)
Bandwidth caps, a limit on the amount of data users can upload and download in a month, are common globally for both home and mobile Internet access. With caps, each bit of data consumed comes at a cost against a monthly quota or a running tab. Yet, relatively little work has considered the implications of this usage-based pricing model on the user experience. In this paper, we present results from a qualitative study of households living with bandwidth caps. Our findings suggest home users grapple with three uncertainties regarding their bandwidth usage: invisible balances, mysterious processes, and multiple users. We discuss how these uncertainties impact their usage and describe the potential for better tools to help monitor and manage data caps. We conclude that as a community we need to cater for users under Internet cost constraints.